The Role of Health Workers in Realizing Community Independence to Prevent Non-Communicable Diseases in Campurejo Community Health Center, Kediri City - Is Fadhillah; Evita Widyawati; Nurita Nilasari (Journal of Ners and Midwifery, 2021)
This study aimed to determine the understanding of health care towards social phenomena related to the dominance of non-communicable diseases which were increased in the community and to identify what efforts were made by health workers in preventing non-communicable diseases. The long-term goal of this study was to control the risk factors for PTM in Indonesia, especially in Campurejo Health Center, Mojoroto District, Kediri City. This study used a qualitative method with 72 populations and 10 samples. The data was collected through purposive sampling and in-depth interviews. The study informants were health workers from Kediri city health office, health workers at the Campurejo Health Center, community leaders and health cadres. The data analysis used interactive qualitative methods (Milles and Hebberman) and the instrument was recorder. The results of the study showed the concept of objectivation in opposing the flow of public understanding of PTM could be seen from the results of the socialization conducted by health workers. This new fact could be seen from one of the efforts of health workers in disseminating PTM in society. Other forms of socialization that were still general in nature could be seen in a variety of activity formats, for example: early detection, health promotion, counseling, mobile Posbindu, and door to door systems. The five micro activities were derived from the grand design of socialization in the perspective of social construction theory as a form of externalization by health workers.